Estudio de factibilidad para la creación de una empresa asociativa para la producción de polvo de asfalto mediante el reciclaje de llantas usadas para la asociación de vulcanizadoras en la ciudad de Quito, sector Calderón - Baéz Bedón, Daniela Alexandra (2015)
This proposal is focused on the contribution of waste disposal given by the disuse of the tires of the vehicles, which are major suppliers Quito's population who have the need to get rid of the accumulation of such waste from their homes. The vulcanizing who the scavenging of these tires and meet retread process, will also benefit because they are the ones who provide the raw materials to the recycling plant, becoming partners in it. The recycler has the suitable machinery to comply with the process of transforming the tires in asphalt dust and to remove wire that will allow them to sell the industrial market. The recycler as an institution is a business association that will bring together 279 centers and vulcanizing who also benefit financially, according to the number of tires that provide the plant. Recycling is economically viable because positive financial indicators such as net present value (NPV) of $ 25,796.64 and an internal rate of return (IRR) of 16.07% was obtained.